Fascicles and the interfascicular matrix show adaptation for fatigue resistance in energy storing tendons. (15th September 2016) - Thorpe, Chavaunne T.; Riley, Graham P.; Birch, Helen L.; Clegg, Peter D.; Screen, Hazel R.C.
Graphical abstract: Abstract: Tendon is composed of rope-like fascicles, bound together by interfascicular matrix (IFM). Our previous work shows that the IFM is critical for tendon function, facilitating sliding between fascicles to allow tendons to stretch. This function is particularly important in energy storing tendons, which experience extremely high strains during exercise, and therefore require the capacity for considerable inter-fascicular sliding and recoil. This capacity is not required in positional tendons. Whilst we have previously described the quasi-static properties of the IFM, the fatigue resistance of the IFM in functionally distinct tendons remains unknown. We therefore tested the hypothesis that fascicles and IFM in the energy storing equine superficial digital flexor tendon (SDFT) are more fatigue resistant than those in the positional common digital extensor tendon (CDET). Fascicles and IFM from both tendon types were subjected to cyclic fatigue testing until failure, and mechanical properties were calculated. The results demonstrated that both fascicles and IFM from the energy storing SDFT were able to resist a greater number of cycles before failure than those from the positional CDET. Further, SDFT fascicles and IFM exhibited less hysteresis over the course of testing than their counterparts in the CDET. This is the first study to assess the fatigue resistance of the IFM, demonstrating that IFM has a functional role within tendon and contributes significantly to tendon mechanical properties. These data provide important advances into fully characterising tendon structure-function relationships. Statement of Significance: Understanding tendon-structure function relationships is crucial for the development of effective preventative measures and treatments for tendon injury. In this study, we demonstrate for the first time that the interfascicular matrix is able to withstand a high degree of cyclic loading, and is specialised for improved fatigue resistance in energy storing tendons. These findings highlight the importance of the interfascicular matrix in the function of energy storing tendons, and potentially provide new avenues for the development of treatments for tendon injury which specifically target the interfascicular matrix.